Problem Politik Media Terhadap Korupsi - Mr Mukhijab (Program Studi Ilmu Komunikasi, 2014)
This article describes the role of the media to support the eradication of corruption in Indonesia, which is displayed in the form of editorial policy of the media in constructing social reality of corruption cases. Two patterns of reconstruction of social reality as a basis editorial policy, which consists of the reconstruction as rewriting and reconstruction as the actualization of the cultural ideology of journalism by working with certain strategies such as news or reconstructing interpretative facts accompanied by a media crew assessment. Its meaning is, the product should be aligned reconstruction of social reality and is able to transform the values of an anti-corruption into public space. The problem is when the national media or local media that makes governments and institutions that have economic and political power as a strategic partner, the media tend to be politically conservative attitudes or rewriting only in constructing a case of corruption by reason of maintaining objectivity the role of the media. That attitude can be used as an indication that the media in a crisis situation in favor of eradication of corruption.